2019
DOI: 10.1051/0004-6361/201832606
|View full text |Cite
|
Sign up to set email alerts
|

Disk origin of the Milky Way bulge: the necessity of the thick disk

Abstract: In the Milky Way bulge, metal-rich stars form a strong bar and are more peanut-shaped than metal-poor stars. It has recently been claimed that this behavior is driven by the initial (i.e., before bar formation) in-plane radial velocity dispersion of these populations, rather than by their initial vertical random motions. This has led to the suggestion that a thick disk is not necessary to explain the characteristics of the Milky Way bulge. We discuss this issue again by analyzing two dissipationless N-body sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…1, top right panel). At t = 5 Gyr, the bar strength starts to decline because of the vertical buckling of the bar and the subsequent formation of a boxy/peanut bulge, as has been reported in a number N-body simulations (Combes & Sanders 1981;Combes et al 1990;Martinez-Valpuesta et al 2006;Athanassoula 2008;Di Matteo et al 2019;Parul et al 2020;Ciambur et al 2020). As a result of the bar slowdown (see Debattista & Sellwood 2000;Athanassoula 2003), its length increases and thereby its resonances migrate outward (see, e.g., Halle et al 2018) because the whole resonance region can be very wide in radius, as shown when an analysis of individual orbits of stars is performed (Ceverino & Klypin 2007;Halle et al 2018;Khoperskov et al 2020).…”
Section: Modelsupporting
confidence: 63%
“…1, top right panel). At t = 5 Gyr, the bar strength starts to decline because of the vertical buckling of the bar and the subsequent formation of a boxy/peanut bulge, as has been reported in a number N-body simulations (Combes & Sanders 1981;Combes et al 1990;Martinez-Valpuesta et al 2006;Athanassoula 2008;Di Matteo et al 2019;Parul et al 2020;Ciambur et al 2020). As a result of the bar slowdown (see Debattista & Sellwood 2000;Athanassoula 2003), its length increases and thereby its resonances migrate outward (see, e.g., Halle et al 2018) because the whole resonance region can be very wide in radius, as shown when an analysis of individual orbits of stars is performed (Ceverino & Klypin 2007;Halle et al 2018;Khoperskov et al 2020).…”
Section: Modelsupporting
confidence: 63%
“…N-body models of b/p bulges built from single thin disks with inside-out population gradients have reproduced several characteristics observed in the Milky Way's b/p bulge, such as cylindrical rotation (Shen et al 2010) or the vertical metallicity gradient (Martinez-Valpuesta & Gerhard 2011). However, these models also miss many of the finer chemo-kinematic properties seen in the bulge (Di Matteo et al 2015Matteo et al , 2019Fragkoudi et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A monotonically increasing vertical profile of JR,0 develops in most models as a result of B/P formation, while the vertical gradient in Jz,0 is largely erased. Both these facts argue that the radial motions are much more important for determining the final vertical thickening of a population, as proposed by Debattista et al (2017), and at odds with the suggestion of Di Matteo et al (2019). Nevertheless, a thick, vertically hot, disc is also likely to be radially hot; as such the combination of a thin and a thick disc is still likely to retain some of the vertical gradient inherent in the different metallicities of the two discs once a bar forms.…”
Section: Kinematic Fractionationmentioning
confidence: 93%
“…For this reason, they proposed that the radial random motion of stars determined the vertical height stars can reach during buckling, with radially hotter stars reaching larger heights. Recently, Di Matteo et al (2019) argued that the vertical dispersion before the bar forms is just as important as the radial dispersion. We have shown here that the vertical thickening of populations is a strongly monotonic function of JR,0, but depends less strongly on Jz,0.…”
Section: Kinematic Fractionationmentioning
confidence: 99%